Hegel’s logical instruction at the Gymnasium Illustre (1776-1778): the textbooks in context - Badenhorst, Daniel (Revista Eletrônica Estudos Hegelianos, 2022)
This article is a contribution to the all too small literature which deals with G.W.F Hegel’s formal logical instruction. Specifically, it looks to clarify the nature, basis and educational context of the logical instruction that Hegel received during his time at the Gymnasium Illustre in Stuttgart (1776–1788). It begins with a brief biographical section where the account of the only other scholar to have significantly contributed to a discussion of the early Hegel’s logical instruction, Riccardo Pozzo, is corrected and updated. It then proceeds to describe the nature of the logic textbooks that Hegel encountered thanks to his early education. In addition to briefly describing the content and notion of logic operative in these textbooks the article also summarily explores the context in which Hegel encountered these particular textbooks and not others. In providing the reader with an interesting and rich documentation of the logical instruction Hegel received at the Stuttgart Gymnasium, the interested party may now explore any of these aspects in greater deal as they consider it relevant, necessary or both. Because of this limitation of scope and the still immature nature of this scholarly debate this paper makes a contribution that ought to be considered documentarian and biographical.
Keywords: Hegel; Philosophical Biography; Logic; Neohumanism; Wolff